PENETAPAN KADAR AIR DAN pH PADA SAMPEL TANAH - Febrianti, Dea (DE FACTO : Journal Of International Multidisciplinary Science, 2025)
Each type of soil has different properties and characteristics, it is important to test the pH and moisture content of the soil to ensure optimal soil quality, soil productivity value and determine appropriate treatment steps. For testing soil moisture content, the gravimetric method is used which refers to work instruction document number 15.4/IK/soil/2020. The research method was potentiometric. The pH value indicates the concentration of H+ ions in the soil solution expressed as -log [H+]. An increase in H+ concentration increases the potential of the solution which is measured by the device and converted to the pH scale. The potential arising is measured based on the potential of the comparison electrode (calomel or AgCl). Usually one electrode is used which already consists of a comparison electrode and a glass electrode (combination electrode). The concentration of H+ extracted with water states the active (actual) acidity while 1 M KCl states the reserve (potential) acidity. Active acidity is caused by H+ ions in the soil solution, while potential acidity is caused by H+ and Al3+ ions found on the soil surface.